2016
DOI: 10.1007/s13659-016-0093-7
|View full text |Cite
|
Sign up to set email alerts
|

Five New Alkaloids from Cephalotaxus lanceolata and C. fortunei var. alpina

Abstract: Five new alkaloids (1–5) were isolated from the leaves and twigs of Cephalotaxus lanceolata and C. fortunei var. alpina along with 24 known alkaloids. The new structures were elucidated based on spectroscopic data including 1D and 2D NMR, FTIR, UV and MS. These new alkaloids showed no cytotoxicity to HeLa, SGC-7901 gastric cancer, and A-549 lung cancer cell lines.Electronic supplementary materialThe online version of this article (doi:10.1007/s13659-016-0093-7) contains supplementary material, which is availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…3) and the similar NMR data to those of the known alkaloid ( 18 ). 22 The NOE correlations of H-4 with H-6 and H-14 suggested that H-4 was α-orientation. The NOE correlations of H-2 with H-10β and H-11 with H-17 indicated that H-2 and the oxygen bridge between C-3 and C-11 were β-orientation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3) and the similar NMR data to those of the known alkaloid ( 18 ). 22 The NOE correlations of H-4 with H-6 and H-14 suggested that H-4 was α-orientation. The NOE correlations of H-2 with H-10β and H-11 with H-17 indicated that H-2 and the oxygen bridge between C-3 and C-11 were β-orientation.…”
Section: Resultsmentioning
confidence: 99%
“…2) supported the above deduction and revealed that the aglycone of compound 17 might be cephalotine A ( 18 ). 22 The key HMBC correlation from H-1′ to C-3 indicated that the sugar was attached to C-3.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 1 and 2 seem to generate from the coisolated epimeric cephalotaxine-type alkaloids, cephalotines A (3) and B (4). 5 Undergoing the hemiacetal transforming cleavage of the hemiacetal between C-3/C-11 in 3 and 4, 5a and 5b were formed. 9 After oxidation at C-11 of 5a and 5b to produce 6a and 6b, an additional ring between C-10 and C-3 might be constructed by the aldol-type reaction to generate fortuneicyclidins A (1) and B (2).…”
mentioning
confidence: 99%
“…Since the discovery of cephalotaxine in 1963, alkaloid contents of most Cephalotaxus species have already been studied . However, the Cephalotaxus alkaloids were mainly classified into cephalotaxine and wilsonine-type skeletons with few other reports. , In order to enrich the library of Cephalotaxus alkaloids, intensive investigations have been made by us on the alkaloid constituents from the seeds of C. fortunei , Hook f. A pair of structurally unique alkaloids, fortuneicyclidins A ( 1 ) and B ( 2 ) (Figure ), with an intriguing 7-azatetracyclo­[5.4.3.0.0 2,8 ]­tridecane core, were obtained, along with two biogenetically relative precursors, cephalotines A ( 3 ) and B ( 4 ) . Herein, we present the detailed experimental procedure, structure elucidation, and biogenetic hypothesis of these two interesting compounds.…”
mentioning
confidence: 99%
See 1 more Smart Citation